Moderating effect of gender on the relationship of personal moral philosophy with ethical decision making: case study on HR practitioners in Malaysia hotel industry - Chan, Ling Meng; Chelliah, Thamil Durai; Othman, Jamilah; Joned, Rosinah (Institut Kajian Dasar Pertanian dan Makanan, Universiti Putra Malaysia, 2015)
The study attempted to examine whether personal moral philosophy is significantly correlated with ethical decision making. Besides that this study intended to investigate the moderating effects of gender and their linked between personal moral philosophy and ethical decision making among human resource practitioners in Malaysia hotel industry. The concern for ethical actions continuously challenges the hotel industry. Interest and complex ethical issues impact this broad business which ranges from restaurant management to senior living to tourism – based operations and beyond. Business ethics remain at the forefront of popular and academic journals as incidents that threaten the ethics fiber of hotel industry. The challenges of human resources practitioners are to exemplify ethical action and to be willing to be held accountable to their management board and to the public for their decision choices (Ardagh & Macklin, 1998). The study attempted to examine whether personal moral philosophy is significantly correlated with ethical decision making. Besides that this study intended to investigate the moderating effects of gender and their linked between personal moral philosophy and ethical decision making among human resource practitioners in Malaysia hotel industry. Results showed that personal moral philosophy and gender differences played significant in ethical judgment. Furthermore, the findings consistently showed that gender influences able to change the ethical belief of HR practitioners in their ethical judgment.